Malignant ascites in pancreatic cancer: Pathophysiology, diagnosis, molecular characterization, and therapeutic strategies - Han, Margaret Y.; Borazanci, Erkut H. (Frontiers in Oncology, 2023)
Malignant ascites is the accumulation of fluid in the peritoneum as a result of advanced cancer and often signifies the terminal phase of the disease. Management of malignant ascites remains a clinical challenge as symptom palliation is the current standard of cure. Previously, studies examining malignant ascites largely focused on ovarian and gastric cancer. In recent years, there has been a significant increase in research on malignant ascites in pancreatic cancer. Malignant ascites is usually diagnosed based on positive cytology, but cytology is not always diagnostic, indicating the need for novel diagnostic tools and biomarkers. This review aims to summarize the current understanding of malignant ascites in pancreatic cancer and the recent advances in the molecular characterization of malignant ascites fluid from patients with pancreatic cancer including analysis of soluble molecules and extracellular vesicles. Current standard of care treatment options such as paracenteses and diuretics are outlined along with new emerging treatment strategies such as immunotherapy and small-molecule based therapies. New potential investigative directions resulting from these studies are also highlighted.